Pengaruh intervensi teknik perlekatan (latch-on) pada saat Di ruang postpartum terhadap frekuensi pemberian asi Tanpa mp-asi selama 3 minggu pertama kelahiran - Tri - Sumaryani; Riri - Novayelinda; Sofiana - Nurchayati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The aim of this research is to determine the effect of intervention about latch-on technique in postpartum ward on the  frequency  of breastfeeding without complementary feeding in the first 3 weeks of birth. The design of this research is "quasy experimental" designed with "post-test only control group". The groups were divided into experimental group and control group. This sample of this study were mothers with normal delivery process in the postpartum ward RSUD Petala Bumi Pekanbaru. The sample consist of 30 mothers who were taken by using purposive sampling technique. The experiment group is provided with  a demonstration latch-on technique allowed by redemonstration session  to the mother and baby. Measuring instruments that used was the questionnaire about frequency of breastfeeding without complementary feeding. The Mann-Whitney test showed p (0.153) > α (0.05) means that latch-on technique intervention in postpartum ward has no effect on the frequencies of breastfeeding without complementary feeding in the first 3 weeks of birth. The result of this study recommended for doing further research about giving intervention latch-on technique with more ensure ability of respondents about the use of latch-on techniques in breastfeeding in the postpartum ward with increase number of interventions that achievement breastfeeding without complementary feeding can also be improved. Keywords   : breastfeeding, complementary feeding, latch-on techniques